2012
DOI: 10.3347/kjp.2012.50.2.173
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Opisthorchis viverrini Infection in a Riparian Population in Takeo Province, Cambodia

Abstract: Opisthorchis viverrini infection was found to be highly prevalent in 3 riverside villages (Ang Svay Chek A, B, and C) of the Prey Kabas District, Takeo Province. This area is located in the southern part of Cambodia, where the recovery of adult O. viverrini worms was recently reported. From May 2006 until May 2010, fecal examinations were performed on a total of 1,799 villagers using the Kato-Katz thick smear technique. In the 3 villages, the overall positive rate for helminth eggs ranged from 51.7 to 59.0% (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 12 publications
2
31
2
Order By: Relevance
“…This was reconfirmed by fecal examinations during the Korea-Cambodia International Collaboration Project on Intestinal Parasite Control in Cambodia (2006-2011) [14,15]. With regard to FBT infections, several investigators have previously reported that O. viverrini are prevalent in some limited areas of Cambodia [14-17].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This was reconfirmed by fecal examinations during the Korea-Cambodia International Collaboration Project on Intestinal Parasite Control in Cambodia (2006-2011) [14,15]. With regard to FBT infections, several investigators have previously reported that O. viverrini are prevalent in some limited areas of Cambodia [14-17].…”
Section: Introductionmentioning
confidence: 78%
“…This was reconfirmed by fecal examinations during the Korea-Cambodia International Collaboration Project on Intestinal Parasite Control in Cambodia (2006-2011) [14,15]. With regard to FBT infections, several investigators have previously reported that O. viverrini are prevalent in some limited areas of Cambodia [14-17]. Recently, Touch et al [17] reported infection of freshwater fish with O. viverrini metacercariae in areas adjacent to the Lake 500 near the border of Kandal and Takeo Provinces, southern Cambodia [17].…”
Section: Introductionmentioning
confidence: 84%
“…Freshwater snails and fish typically serve as the intermediate host in most instances [1,6,14,15]. These trematodes are endemic throughout the Southeast Asian region, including Thailand, Lao PDR, Vietnam, Korea and the Philippines [1,2,5,7,10,15], with a high incidence of mixed infections involving small liver trematodes and other minute intestinal trematodes [16,17]. The distribution of trematodes requires specific suitable ecological conditions, typically involving certain water resources such as those located in agricultural areas as well as rivers and irrigation canals.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the liver fluke, a high parasitic prevalence has been recorded in some provinces, especially in Kampong Cham, Kampong Thom, Kandal, Kratie, and Takeo provinces. In these regions, infestation rates among the general population range from 1.3 to 65.1% [19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%